Human fetal lung mesenchymal stem cells ameliorate lung injury in an animal model - Mahtab Golmohammadi; Mohammad Hasan Sheikhha; Fatemeh Ganji; Ali Shirani; Mahmood Barati; Seyed Mehdi Kalantar; Seyed Mohammad Amin Haramshahi; Nushin Karkuki Osguei; Ali Samadikuchaksaraei (Scientific Reports)
Abstract Acute lung injury (ALI) is a critical condition with limited treatment options. This study evaluates the therapeutic potential of human fetal lung-derived mesenchymal stem cells (hFL-MSCs) in an experimental model of ALI. Our proof-of-concept findings suggest a paradigm shift in the approach to cell sourcing for lung diseases, proposing that fetal lung cells may be potential targets for stem cell differentiation studies when the derived cells are intended to be used for lung cell therapy. After characterizing hFL-MSCs, 18-week fetal lung cells were intratracheally instilled into rats with bleomycin-induced ALI. All the animals were evaluated on days 3 − 28 post-injury for cell count and the cytokines in bronchoalveolar lavage fluid (BALF), lung wet/dry weight ratio, lung tissue histological staining and expression of an extracellular matrix component, inflammatory and fibrotic genes. The findings confirm mesenchymal stem cell identity of the isolated cells and stability in their cell cycle distribution. Analysis of BALF showed that immune cell response to acute inflammation and adaptive immunity was significantly ameliorated by cell therapy with hFL-MSCs. Same results were confirmed by the levels of IL-6, TNF-α, IL-10 and NO in BALF, the lung wet/dry weight ratio and histopathological analysis of lung tissues after H&E and Masson’s trichrome staining. Effective modulation of key pro-inflammatory (Il6, Tnf, Il1b), pro-fibrotic (Tgfb1) and Col1a1 genes were also confirmed after therapy with hFL-MSCs. Our findings suggest that fetal lung tissue-specific stem cells are viable options for lung cell therapy and could be considered as targets for engineering of regenerative cells for lung diseases.